2021
DOI: 10.3389/fpsyg.2021.673529
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Burst Suppression EEG Patterns

Abstract: Burst-suppression electroencephalography (EEG) patterns of electrical activity, characterized by intermittent high-power broad-spectrum oscillations alternating with isoelectricity, have long been observed in the human brain during general anesthesia, hypothermia, coma and early infantile encephalopathy. Recently, commonalities between conditions associated with burst-suppression patterns have led to new insights into the origin of burst-suppression EEG patterns, their effects on the brain, and their use as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 76 publications
0
54
0
1
Order By: Relevance
“…Standardizing burst suppression measurement is crucial to decreasing variability, as one study found that different interelectrode distances produce different burst durations (Moldovan et al, 2016). Measurement is also challenging since burst suppression patterns are inherently irregular-observed "spectral drifts" in bursts suggest that burst suppression may be more variable rather than a strict on-off switch of the EEG signature (Ching et al, 2012;Lewis et al, 2013;Liley and Walsh, 2013;Shanker et al, 2021).…”
Section: Burst Suppression Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Standardizing burst suppression measurement is crucial to decreasing variability, as one study found that different interelectrode distances produce different burst durations (Moldovan et al, 2016). Measurement is also challenging since burst suppression patterns are inherently irregular-observed "spectral drifts" in bursts suggest that burst suppression may be more variable rather than a strict on-off switch of the EEG signature (Ching et al, 2012;Lewis et al, 2013;Liley and Walsh, 2013;Shanker et al, 2021).…”
Section: Burst Suppression Detectionmentioning
confidence: 99%
“…Under these conditions, there are low levels of ATP, which may lead to protection of membrane integrity and cellular preservation (Forgacs et al, 2020). An important aspect of this hypothesis is that it can be applied to scenarios of decreased metabolic activity such as general anesthesia, hypothermia, and brain injury (Rampil, 1998;Ching et al, 2012;Shanker et al, 2021).…”
Section: Rojas Et Al 2008)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows normal EEG signal and BS signal within 10 seconds under general anesthesia, which were intercepted by the EEG signal analysis software eeglab. BS does not occur during physiological sleep, excessive anesthesia and age are the main factors leading to BS [11,12] . The occurrence of BS decreases the metabolic rate of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [2017] found propofol induced extremely steep 1/f slopes, and Colombo et al [2019] correlated steeper 1/f slopes with increasing degrees of unresponsiveness/unconsciousness from anesthesia. General anesthesia has been shown to cause cortex-wide synchronized bursting selectively in the layer V pyramidal cells [Bharioke et al, 2022] resulting in a state clinically referred to as burst-suppression [Steriade et al, 1994, Shanker et al, 2021. While bursting is grossly synchronized, there has been local variability in burst-onset time noted [Lewis et al, 2013].…”
Section: Introductionmentioning
confidence: 99%